Conceptualising the 'community' as a recipient of money – A critical literature review, and implications for health and inequalities. (October 2015) - Reynolds, Joanna; Egan, Matt; Renedo, Alicia; Petticrew, Mark
Abstract: There is increasing attention on how money may bring about positive changes to health, and money-based development approaches are becoming more commonplace at the 'community' level, including in high-income countries. However, little attention has been paid to how the 'community' might be varyingly conceptualised in these scenarios, or to the potential implications of this for interpreting the impacts of such health improvement approaches. This paper presents a critical interpretive review of literature presenting different scenarios from high-income countries in which the 'community' receives money, to explore how 'community' is conceptualised in relation to this process. Some texts gave explicit definitions of 'community', but multiple other conceptualisations were interpreted across all texts, conveyed through the construction of 'problematics', and descriptions of how and why money was given. The findings indicate that the flow of money shapes how conceptualisations of 'community' are produced, and that the implicit power relations and inequalities can construct and privilege particular sets of identities and relationships throughout the process. This highlights implications for approaching public health evaluations of giving money to 'communities', and for better understanding how it might bring about change to health and inequalities, where the 'community' cannot be interpreted merely as a setting or recipient of such an intervention, but something constructed and negotiated through the flow of money itself. Highlights: Focuses on interventions giving money to communities in high-income settings. Examines multiple conceptualisations of community across those interventions. Shows that flow of money and existing inequalities shape constructions of community. Describes implications for evaluations of impact of money on health inequalities.